THE PROFITABILITY OF LENTIL CULTIVATED AS MIXTURES WITH BARLEY OR OAT - Jolanta Bojarszczuk; Jerzy Księżak (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2024)
The aim of the study was to evaluate the economic efficiency of lentil at different mixtures in ecological system. The study was based on the results of a two-year field study in 2022-2023, conducted at the Agricultural Experimental Station in Grabów, belonging to the Institute of Soil Science and Plant Cultivation in Puławy. This study evaluated effect of growing the lentil (Lens culinaris Medic.) with barley (Hordeum vulgare L.) or oats (Avena sativa L.) as a supporting plant impacts the yield of lentil. The one-factor experiment was set up as a randomized blocks design with four replicates in ecological conditions. The study showed that higher seeds/grain yield was obtained under the mixtures method, where a supporting crop was used than in sole cropping. The gross margin, as the difference between the value of seeds/grain yield and direct and indirect costs prepared for each cultivation system of lentil, showed definite differences. Analysis found that the highest gross margin was obtained under cultivation of lentil with oat (3,653.3 PLN/ha), while the lowest under cultivation lentil in pure sowing (695.3 PLN/ha), which determinated by level of yielding. The level of the gross margin was more impacted by the level of the obtained yield and the cost of agrotechnical treatments than by the level of other direct costs. The highest rate of direct profitability without subsidies (profitability) determined as the relation of production value of lentil seeds/grain to direct costs determined based relation production value of seeds/grain to direct cost was obtained under cultivation legume with oat (1.50).